1997
DOI: 10.1046/j.1365-2567.1997.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell epitopes recognized within the 65 000 MW hsp in patients‘qc with IgA nephropathy

Abstract: SUMMARYIgA nephropathy (IgAN ) is the commonest cause of glomerulonephritis and clinical exacerbation of IgAN is frequently associated with mucosal infection. T-cell receptorcd ( TCRcd+) cells are increased in both the circulation and in renal biopsies of patients with progressive IgAN. We examined the hypothesis that specific peptides within the 65 000 MW heat-shock protein (hsp) might stimulate TCRcd cells and play a part in the immunopathogenesis of IgAN. We studied T-cell proliferative responses stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…Recent investigations also support a possible role for HSP 47, 65, 70, and 90 in the pathogenesis of some forms of glomerulopathy (122,123,125). Work by Warr and colleagues suggests that cross reactivity between microbial and human HSPs may stimulate a T cell subset that has been implicated in the pathogenesis of progressive IgA nephritis in humans (124). In this study, a peptide derived from mycobacterial HSP 65 stimulated T cell proliferation.…”
Section: Glomerulonephritis (Gn) and Immune-mediated Injurysupporting
confidence: 52%
See 2 more Smart Citations
“…Recent investigations also support a possible role for HSP 47, 65, 70, and 90 in the pathogenesis of some forms of glomerulopathy (122,123,125). Work by Warr and colleagues suggests that cross reactivity between microbial and human HSPs may stimulate a T cell subset that has been implicated in the pathogenesis of progressive IgA nephritis in humans (124). In this study, a peptide derived from mycobacterial HSP 65 stimulated T cell proliferation.…”
Section: Glomerulonephritis (Gn) and Immune-mediated Injurysupporting
confidence: 52%
“…The presence of constitutive and inducible stress proteins has been demonstrated in animal kidneys with experimental GN (120)(121)(122). An increase in stress proteins was detected in human kidneys with various forms of acute GN (120,(123)(124)(125). Proteinuria, a potential cause of renal tubular injury that often accompanies GN, increases the expression of HSP 72 (123).…”
Section: Glomerulonephritis (Gn) and Immune-mediated Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that γδ T cells in the gut of IgAN patients mainly use a subset of γδ T cells 21 . Furthermore three peptides within a 65 000‐MW heat shock protein were recognized by T cells from IgAN patients and also upregulated the T‐cell proliferative response by increasing the γδ T‐cell subsets 22 . In the present study we have further demonstrated an oligoclonal population of Vδ1 bearing a motif in their CDR3 region in most IgAN kidneys examined.…”
Section: Discussionsupporting
confidence: 67%
“…It has been reported that V γ 9+ T cells proliferated in response to various antigens, including mycobacterium tuberculosis, staphylococcus enterotoxin B, and bacterial heat shock protein (hsp) [31]. It has also been reported that a subset of γδ T cells in IgAN patients could recognize the epitopes of the human hsp65 [32]. Since human hsp shares a high degree of homology with hsp of microorganisms, it is likely that V γ 9+ T cells in IgAN patients proliferate in response to bacterial hsp delivered from mucosal infection by microorganisms.…”
Section: Discussionmentioning
confidence: 99%